What is the role for molecular genetic data in public policy? - Steven F. Lehrer; Weili Ding (IZA World of Labor, 2017)
Both the availability and sheer volume of data sets containing individual molecular genetic information are growing at a rapid pace. Many argue that these data can facilitate the identification of genes underlying important socio-economic outcomes, such as educational attainment and fertility. Opponents often counter that the benefits are as yet unclear, and that the threat to individual privacy is a serious one. The initial exploration presented herein suggests that significant benefits to the understanding of socio-economic outcomes and the design of both social and education policy may be gained by effectively and safely utilizing genetic data.
Keywords: 330; genetic markers; gene–environment interactions; genome-wide association studies; intergenerational transmission